Group portrait of the attendees of a 1947 Degree of Pocahontas meeting in San Jose, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of a Degree of Pocahontas meeting, held August 18-21, 1947 in San Jose, California.